The Effect of Simultaneous Si and Ti/Mo Alloying on High-Temperature Strength of Fe3Al-Based Iron Aluminides - Věra Vodičková; Martin Švec; Pavel Hanus; Pavel Novák; Antonín Záděra; Vojtěch Keller; Petra Pazourková Prokopčáková (Molecules, 2020)
The effect of phase composition and morphology on high-temperature strength in the compression of Fe-Al-Si-based iron aluminides manufactured by casting was investigated. The structure and high-temperature strength in the compression of three alloys—Fe28Al5Si, Fe28Al5Si2Mo, and Fe28Al5Si2Ti—were studied. Long-term (at 800 °C for 100 h) annealing was performed for the achievement of structural stability. The phase composition and grain size of alloys were primarily described by means of scanning electron microscopy equipped with energy dispersive analysis and Electron Backscatter Diffraction (EBSD). The phase composition was verified by X-ray diffraction (XRD) analysis. The effect of Mo and Ti addition as well as the effect of long-term annealing on high-temperature yield stress in compression were investigated. Both additives—Mo and Ti—affected the yield stress values positively. Long-term annealing of Fe28Al5Si-X iron aluminide alloyed with Mo and Ti deteriorates yield stress values slightly due to grain coarsening.